Pengaruh Kecerdasan Intrapersonal Dan Kemandirian Belajar Terhadap Kemampuan Berpikir Kreatif Pada Pelajaran Matematika - Maratusyolihat Maratusyolihat; Nida Adillah; Miftahul Ulfah (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
This study aims to determine the effect of intrapersonal intelligence and learning independence on the ability to think creatively in mathematics. Research place at MTs Serang district. This research method uses a survey method, with a sample of 83 people. The sampling technique uses multi-stage sampling. Collecting data using essay tests and questionnaires. Hypothesis testing using path analysis (path analysis). The results of the study concluded that there was a significant influence of intrapersonal intelligence and learning independence on the ability to think creatively in mathematics. More effectively improve the ability to think creatively is done by awakening the independence of learning first in mathematics. So that students easily grasp the material being taught and students will be more motivated and happy in learning because they are already familiar with the learning system